2023
DOI: 10.3390/ph16010079
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Micro-Ribbons and Micro-Fibres in the Formulation of 3D Printed Fast Dissolving Oral Films

Abstract: Three-dimensional printing (3DP) allows production of novel fast dissolving oral films (FDFs). However, mechanical properties of the films may not be desirable when certain excipients are used. This work investigated whether adding chitosan micro-ribbons or cellulose microfibres will achieve desired FDFs by fused deposition modelling 3DP. Filaments containing polyvinyl alcohol (PVA) and paracetamol as model drug were manufactured at 170 °C. At 130 °C, filaments containing polyvinylpyrrolidone (PVP) and paracet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The observed short disintegration time for 3D-printed films could be due to the higher surface roughness compared to solvent-cast films, allowing more exposure of the 3D-printed films to the disintegration media. Interestingly, PVA films disintegrated within 71 ± 12 s, which was shorter than the disintegration time for pure PVA films reported by Algellay et al (2023). The difference could be due to the use of different disintegration techniques: Algellay et al ( 2023) employed a tablet disintegration equipment, whereas Lee et al (2022) used a Petri dish method.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The observed short disintegration time for 3D-printed films could be due to the higher surface roughness compared to solvent-cast films, allowing more exposure of the 3D-printed films to the disintegration media. Interestingly, PVA films disintegrated within 71 ± 12 s, which was shorter than the disintegration time for pure PVA films reported by Algellay et al (2023). The difference could be due to the use of different disintegration techniques: Algellay et al ( 2023) employed a tablet disintegration equipment, whereas Lee et al (2022) used a Petri dish method.…”
mentioning
confidence: 89%
“…Algellay et al (2023) examined the use of micro-ribbons in FDM 3D-printed fast-dissolving oral films to improve the mechanical strength and disintegration time of printed films while using low-melting-temperature polymers. They found that only hydrophilic micro-ribbons of chitosan were able to improve the disintegration time of the films at low concentrations, perhaps by creating a network of hydrophilic channels within the films [14]. FDM 3D-printed oral films were also investigated by Lee et al (2022) [15].…”
mentioning
confidence: 99%
“…Typically, the dissolution rate of tablets printed by FDM is relatively slower than that of ink-jet-printed IR tablets, probably due to the compactness of the used polymer and the cured molten materials. Therefore, to achieve IR behavior, the porosity of tablets should be increased by selecting the appropriate polymer and changing the filling rate of tablets during FDM printing [ 167 ]. Kempin et al used the heat-sensitive drug pantoprazole sodium as a model drug.…”
Section: Pharmaceutical Dosage Forms By 3dpmentioning
confidence: 99%